Características cognitivas e desempenho em tradução: investigação em tempo real - Rui Rothe-neves (2002)
This study deals with assessing the relationship between performance in translation and some cognitive features, specially working memory Two other objectives were to verify whether that relationship differs as a result of previous expenence in translation, and in other related tasks (copying, reading and writing) In order to do that, three empirical studies were carried out using process data from translations. Study 1 proposed to verify the suitability of data collection procedures and was based on data from 22 undergraduate students of Translation and Enelishlanguage at UFOP. In study 2. the correlations between working memory L2 experience with computers, and performance features of reading, writing' and translating were assessed on data from six FALE-UFMG undergraduate students and SIX professional translators. In study 3, the translations produced in the previous study were assessed by independent judges on the basis of common parameters, and the correlation between translation quality and cognitive featureswas investigated. For data gathering purposes it was necessary to develop a procedure based on previous research about individual differences and the translation process. The results threw Ught on the relationship between working memory and performance in translation among professionals, concerning process efficiency as weU as the quality of the product. There was also a relationship betweenworking memory and reading in L2. Professionals and beginners showed clearly distinct cognitive profiles in all tasks. Among working memory factors, processing speed was the trait most directly involved in the investigated tasks; coordination capacity was also related to them, but not storage capacity. In sum, this thesis suggests that working memory may play a role in translation performance, but it is not the most important cognitive feature required by the task. Translating is a complex process, whose specific aspects require different abilities, and furtherstudies should investigate the role of executive functioning and meta-cognitive abilities.